Analisis SWOT dan Manajemen Lingkungan Green Building IPAL Jambi - Adriansyah, Endi; Suzana, Asih; Dony, Wari; Sufra, Rifqi; Selvita, Selvita; Nalendra, Brama (Universitas Batanghari, 2025)
The decline in water quality has had an impact on the surrounding community and the receiving water body (river). To minimize this impact, IPAL (Wastewater Treatment Plant) technology is needed, the IPAL in Jambi city is an IPAL with MBBR technology, its management analysis is needed, both technical and non-technical. The purpose of this study is to analyze internal and external factors and the right strategy for liquid waste management in Jambi using SWOT analysis. In this study, the method used is SWOT analysis to determine the management strategy of IPAL (Wastewater Treatment Plant) in Jambi through observation, and interviews with respondents around the research location. The results of the study show that IPAL (Wastewater Treatment Plant) in Jambi has a role and benefits in waste processing, the treated water is suitable for discharge into the receiving body (river) and meets environmental standards, and is the right solution, becoming a model for other provincial areas in wastewater processing and management.